Fault isolation of thrusters under redundancy in frame-structure unmanned underwater vehicles. (23rd April 2018) - Liu, Fuqiang; Xu, Demin; Yu, Jin; Bai, Long
This article deals with fault isolation issue for the redundant thrusters of frame-structure unmanned underwater vehicles (UUVs). Consistency check is adopted to accomplish this task while solving the reformed control input equations that are produced after getting rid of some fault-free terms from the given equations. Specially selected column vectors from the given control matrix together with the corresponding hypothetical thrust output faults are taken as the known/unknown elements for these equations. Redundant relations among the thrusters support the vector selection, which are revealed by analyzing the maximally linearly independent vectors of the given control matrix. Simulation with faulty thrusters under redundancy in a frame-structure unmanned underwater vehicle illustrates the effectiveness of the proposed methodologies.